2021
DOI: 10.1002/dvdy.344
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA miR‐33 is a pleiotropic regulator of metabolic and developmental processes in Drosophila melanogaster

Abstract: Background: miR-33 family members are well characterized regulators of cellular lipid levels in mammals. Previous studies have shown that overexpression of miR-33 in Drosophila melanogaster leads to elevated triacylglycerol (TAG) levels in certain contexts. Although loss of miR-33 in flies causes subtle defects in larval and adult ovaries, the effects of miR-33 deficiency on lipid metabolism and other phenotypes impacted by metabolic state have not yet been characterized. Results:We found that loss of miR-33 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…For B. mori miRNAs, we found that there was significantly decreased in the number of miRNAs in the silkworm embryos and larvae exposed to the congenital N. bombycis challenge, compared with uninfected embryos and larvae. Both miRNA-33 and miRNA-122, which can target lipid metabolism genes to reprogram host lipid metabolism [68][69][70], are down-regulated during the congenital N. bombycis infection. miR-276 is associated with amino acid metabolism [71], which is down-regulated during the congenital N. bombycis infection.…”
Section: Discussionmentioning
confidence: 99%
“…For B. mori miRNAs, we found that there was significantly decreased in the number of miRNAs in the silkworm embryos and larvae exposed to the congenital N. bombycis challenge, compared with uninfected embryos and larvae. Both miRNA-33 and miRNA-122, which can target lipid metabolism genes to reprogram host lipid metabolism [68][69][70], are down-regulated during the congenital N. bombycis infection. miR-276 is associated with amino acid metabolism [71], which is down-regulated during the congenital N. bombycis infection.…”
Section: Discussionmentioning
confidence: 99%
“…For B. mori miRNAs, we found that there was signi cantly decreased in the number of miRNAs in the silkworm embryos and larvae exposed to the congenital N. bombycis challenge, compared with uninfected embryos and larvae. Both miRNA-33 and miRNA-122, which can target lipid metabolism genes to reprogram host lipid metabolism [53][54][55], are down-regulated during the congenital N. bombycis infection. miR-276 is associated with amino acid metabolism [56], which is downregulated during the congenital N. bombycis infection.…”
Section: Discussionmentioning
confidence: 99%
“…The conserved microRNA, miR-1, for example, has been shown to regulate a number of targets that impact heart structure and function in Drosophila, with implications for human health [38][39]. The conserved microRNA, miR-33, on the other hand, has been established as a key regulator of glucose and lipid metabolism [40][41]. In addition, several microRNAs, such as miR-34 and let-7, are conserved between Drosophila and humans and have been connected to longevity through a variety of mechanisms including, neuronal dysregulation, insulin/TOR signaling, and mitochondria maintenance/ROS production [42].…”
Section: Introductionmentioning
confidence: 99%